Ride Sharing & Data Privacy: How Data Handling Affects the Willingness to Disclose Personal Information - Carsten Hesselmann; Jan Gertheiss; Jörg P. Müller (Findings)
Digital services like ride sharing rely heavily on personal data, e.g. name or age, as individuals have to disclose personal information in order to gain access to the market. This information is exchanged with other participants; yet, the service provider usually gives little to no information regarding the privacy status of the disclosed data. To further investigate the implications of this, we conducted an online survey asking participants about their willingness to disclose personal information under varying privacy status. The results of 127 complete responses show that differences in information privacy settings influence the participants’ willingness in a significant way.